No place for abuse : biblical & practical resources to counteract domestic violence - Kroeger, Catherine Clark; Nason-Clark, Nancy, 1956- (Downers Grove, IL : IVP Books, 2010)
In this revised and updated edition, Catherine Clark Kroeger and Nancy Nason-Clark share with readers a further ten years of experience in listening to the voices of women from around the world and especially to those within the church. They help us hear their cries and find concrete ways to respond so that no home will be a place of abuse. --from publisher description
The prevalence an severity of abuse against women -- Beginning to respond -- Growing in compassion -- Steeple to shelter: paving the pathway -- Searching the scriptures -- Man and woman: dimensions of their union -- Does the suffering of an abused woman bring salvation to her husband? -- A concern for the Christian family?: the dangers of idolization and idealization -- Repentance and forgiveness -- Issues of abuse and authority -- Good news for and about abusers -- The biblical option of divorce -- What can church folk do? -- Taking action: web-base and print resources to assist pastors and congregations.
Includes bibliographical references (p. [229]-249).
Keywords: Church work with dysfunctional families; Family violence -- Religious aspects -- Christianity